SOIL NUTRIENT LOSS THROUGH EROSION CAUSES ECONOMIC LOSS IN THE DELI WATERSHED UPSTREAM - Nurmala Fitri; Aceng Hidayat; Ahyar Ismail (Jurnal Solum, 2022)
Soil erosion generally occurs in areas with steep slopes, especially in mountainous regions, such as the upstream of Deli Watershed located in the administrative area of Karo Regency and Deli Serdang Regency, North Sumatra Province, Indonesia. Apart from the biophysical form of the land, this area also tends to have a higher rainfall level than other lower sites. In addition, the condition of the land surface that lacks green vegetation, such as forests, may lead to erosion. The loss of soil particles, in turn, has the potential to eliminate soil nutrients that act as inputs for agricultural production. Therefore, this study aimed to calculate the average erosion upstream of the Deli watershed and estimate the value of the economic loss of soil nutrient loss due to erosion. The Universal Soil Loss Equation (USLE) Method and the Replacement Cost Method were used. The analysis results showed that the average erosion of the Deli Watershed upstream was 583.02 tonnes/ha/year, which is classified as very heavy erosion. At the same time, the economic loss value for replacing soil nutrients was Rp 2,072,636,100 per ha. Hence, it shows the application of Soil and Water Conservation (KTA) is needed to reduce economic losses due to environmental degradation.Key words : erosion, nutrient loss, replacement cost, USLE